BLINDNESS AND REHABILITATION CONCERNS AMONGST PUPILS OF A SPECIAL EDUCATION CENTRE IN SOUTHWESTERN NIGERIA - O.O, Jagun; M.A, Akinola; O.O, Betiku; O.F, Salami (International Journal of Research -GRANTHAALAYAH, 2019)
Background: Blind Children require access to quality rehabilitation services to optimize function and reduce their disabilities. This may be difficult if competent educators are not available in special education centers in developing countries. Method: A prospective study carried out on consenting parents and pupils at a special education center in South western Nigeria. Results: Sixty-two blind eyes from 31 participants were examined. 25.8% [16] had Optic atrophy, 16.1% [10] had complicated cataracts, 12.9% [8] had Cornea related blindness, 9.7% [6] had End stage Glaucoma, another 9.7% [6] had Phthisis bulbi while the last 25.85% [16] were classified as Others. 94.1% of the educators had undergone Special educational training over the last 20 years but only 11[64.7%] had attended any refresher course over the last 5 years to update theirs teaching skills and only 11.8% had easy access to Online study materials for research and training. Academic skills were taught by all teachers with all students being able to read and write in Braile but recreational skills were least taught in the school. Conclusion: A need for strong Governmental and Non-governmental advocacy to support training of Special educators and to integrate parental education in the Rehabilitation process.